Statut Grada i otoka Korčule 1214./1265. i pitanje dis/kontinuiteta starog i novog konstitucionalizma - Bačić, Arsen (Array, 2018)
In classic natural law the issue of constitution was related to the laws, institutions and practice of organising and directing states and the political system. According to this understanding, every political system of town-state had a constitution. The contemporary meaning of constitution nevertheless gained specific and valuable foundation: today the constitution means the establishment of a special form of political organisation. Contemporary constitutions talk of limited government. With a constitution, political power is constituted and limited at the same time. Some states are constitutional because they have a limited and responsible government and others are not. In the latter case, we are talking about states that have a constitution, but do not have constitutionalism. After civil revolutions, constitutionalism becomes the central mechanism of control of political power and ensuring freedom. This text opens up the question of whether the Statute of Korčule of the year 1214/1265, as a normative projection of municipal organs in the Town and Island of Korčula (assembly of all people, duke, grand council, small council, curia, utility services...), provided the base for researching the (dis)continuity of „ancient constitutionalism“ and classic rational, uniform and contractualistic forms of modern constitutionalism which is based on the constitution as the highest legal act and court control of constitutionality. In conclusion, the Statute of the Town and Island of Korčula, as a unique normative crossword puzzle of medieval institutions, special freedoms and multi-level jurisdictions, represented a real historical platform. From this platform all those bearers of power who implemented power could be controlled and balanced either within legal boundaries or they strived for absolutism and corruption.